'The woods is a more free space for children to be creative; their imagination kind of sparks out there': exploring young children's cognitive play opportunities in natural, manufactured and mixed outdoor preschool zones. Issue 2 (2nd April 2016) - Zamani, Zahra
ABSTRACT: Outdoor preschools are critical for children's play and development. Integrating observational and interview methods, this study examined four-to-five-year-old children's cognitive play experiences in an outdoor preschool with natural, mixed and manufactured zones. The observational results indicated that the natural and mixed zones offered a diverse spectrum of cognitive play, were supportive of different learning styles and expanded their understanding about the world. Children preferred the diverse, challenging and constantly evolving natural settings in these zones. Integrating diverse natural and manufactured settings with loose elements, the mixed zone supported considerable opportunities for functional, exploratory and games with rules play behaviors. The accessible loose materials inspired children's imagination, social engagement and games. In contrast, the manufactured zone offered the most functional and non-play behaviors, and was perceived as an unexciting, predictable and tedious environment. The findings suggest incorporating natural features and settings in outdoor preschools to support a diverse spectrum of cognitive play.